(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation. This article explores the topic of “the formation and use of Labor resources”. Labor resources are one of the main components of the economy, and their effective formation and management are important in the development of each country. The article examines the processes of formation of labor resources, their types, as well as the influence of changes in the labor market and global economic conditions.